A Comprehensive Review of Sunscreen: Formulation Approaches, Active Ingredients, Skin-Type-Based Selection, Nanotechnology, and Regulatory Considerations - Ganpur Pooja; Khandagale Saksh; Gupta Ankita; Prasad Nitish; Jaiswal Tara; Ghadge Ojaswi (Asian Journal of Pharmaceutical Research and Development, 2026)
Excessive exposure to ultraviolet (UV) radiation is a major contributor to acute and chronic skin damage, including Sun burn, premature aging, immune suppression, ocular damage, heat-related illnesses, and the development of melanoma and non- melanoma skin cancers. Sunscreens play a critical role in photoprotection by minimizing UV-induced harm through absorption, reflection, and scattering of radiation. This review comprehensively examines the classification of sunscreens into organic, inorganic, and systemic agents, along with their mechanisms of photoprotection and ideal physicochemical characteristics. Special emphasis is placed on skin-type-based selection of sunscreen formulations, highlighting suitable products for oily, acne-prone, dry, sensitive, post-procedure, pediatric, and pregnant populations. Various dosage forms, including creams, lotions, gels, sprays, and sticks, are discussed with respect to their advantages and limitations. The role of excipients in enhancing stability, safety, spreadability, and user acceptability is critically reviewed. Emerging strategies such as oral and injectable photoprotective agents, including Polypodiumleucotomos extract, nicotinamide, and afamelanotide, are explored for their adjunctive benefits in UV protection and skin cancer prevention. Advances in nanotechnology, particularly the use of nanosized titanium dioxide and zinc oxide, are discussed with respect to formulation improvement, safety, and regulatory concerns. The review also outlines global and Indian regulatory frameworks governing sunscreen products, along with evaluation parameters such as SPF determination, stability testing, and quality assessment. Overall, this review provides an integrated scientific perspective to support evidence- based sunscreen formulation, selection, and regulatory compliance for effective photoprotection.